2002
DOI: 10.1139/l01-089
|View full text |Cite
|
Sign up to set email alerts
|

Velocity distribution in decelerating flow over rough surfaces

Abstract: An experimental program was undertaken to study turbulent boundary layers formed in decelerating open channel flows. The flows over a smooth surface and three rough surfaces were examined. Tests were conducted at a subcritical Froude number (~0.2) and varying depth Reynolds numbers (64 000 < Red < 88 000). The corresponding momentum thickness Reynolds numbers were small (1000 < Reθ < 2100). The velocity measurements were undertaken using a one-component laser-Doppler anemometer. Variables such as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 22 publications
0
14
1
Order By: Relevance
“…Such noise level is realistic since Muste et al [7] have shown that the mean velocity can be measured within 3.5% in normal conditions and up to 10% in adverse (less visibility) conditions. Balachandar et al [27] have also demonstrated that the free-surface velocity can be measured within 2%. Similar analysis shows that the level of perturbation on the value of the velocity ratio () induces an error of comparable order of magnitude as the perturbed value in the reconstruction process.…”
Section: Sensitivity Analysismentioning
confidence: 91%
“…Such noise level is realistic since Muste et al [7] have shown that the mean velocity can be measured within 3.5% in normal conditions and up to 10% in adverse (less visibility) conditions. Balachandar et al [27] have also demonstrated that the free-surface velocity can be measured within 2%. Similar analysis shows that the level of perturbation on the value of the velocity ratio () induces an error of comparable order of magnitude as the perturbed value in the reconstruction process.…”
Section: Sensitivity Analysismentioning
confidence: 91%
“…Similarly, El-Samman [3], studied velocity distribution using artificial vegetation and recommended that furthermore analysis is required to investigate the phenomenon of directing the flow towards the right side in a channel. Velocity distributions with fully developed, steady and uniform flows in open channels with roughed surfaces, have been reported extensively by several researchers [4][5][6][7][8].…”
Section: Althoughmentioning
confidence: 99%
“…It is assumed that each element of the boundary influences the velocity of an arbitrary point in the channel section. Then, the total effect can be integrated along the boundary using the concept of line integral as u = boundary f (r).dP (2) where u is the streamwise velocity at a point in the channel section, f (r) is a velocity function similar to the conventional velocity profiles f (y), and dP is vector notation for a boundary element in the normal direction. In fact, function f in f (r ) and f (y) is unique.…”
Section: Dimensionless Isovel Contoursmentioning
confidence: 99%
“…It was placed at 4.8 m away from the beginning of the channel inlet. In this study, the roughness height (k s ) is taken as the median diameter, d 50 , for the two sand roughened surfaces [2]. In each case, data were collected for four aspect ratios of B/H = 4, 2, 1.33 and 1.…”
Section: Experimental Set-upmentioning
confidence: 99%
See 1 more Smart Citation